The problem of participation of persons with disabilities in the labor market - Sztyler, Jacek (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2016)
The author pays particular attention to participation in the production process of people with disabilities. It highlights a number of important points the moral, psychological and philosophical nature, accompanying the establishment of relations of employers and people with disabilities. Notes the stability of employment of people with secondary and higher education and women. At the same time there is a significant proportion of people with disabilities, who for various reasons are not ready or do not want to look for a job, that is a certain social and economic problem for society. To solve these problems requires a government program.